Exploring the potential of ginseng glycoprotein to improve learning and memory in mice via Notch signaling pathway and structural analysis using multi-information fusion based on liquid chromatography-mass spectrometry. (1st March 2023) - Fang, Xiaoxue; Zhang, Xiaoying; Zhang, Yegang; Zhang, Xun; Shan, Mengyao; Guan, Shuguang; Qiu, Zhidong; Zhu, Difu; Luo, Haoming
Abstract: Ethnopharmacological relevance: Panax ginseng C.A. Meyer reportedly exhibits various beneficial pharmacological activities. Panax ginseng glycoproteins (PGG) are a class of glycosylated protein components extracted from ginseng and can exert significant activity for improving learning and memory abilities. Aim of the study: The objective of the present study was to investigate the PGG-mediated protective mechanism against neurodegenerative diseases via the Notch signaling pathway using proteomic methods. Materials and methods: We examined learning and memory in mice using the Morris water maze and nest-building paradigms. The PGG structure was determined using multi-information fusion based on liquid chromatography-mass spectrometry (LC/MS). Accurate glycosylation sites of glycoproteins were identified using the advanced glycosylation analysis software Byonic. Furthermore, connection modes of the oligosaccharide chain were clarified by methylation analysis of sugar residues. The differentially expressed proteins (DEPs) between wild-type (WT) and APP/APS1 mice were measured and compared using label-free quantitative proteomics, and related signaling pathways were identified. For validation, we performed a series of in vitro tests, including an assessment of cell viability, apoptosis assay, quantitative real-time polymerase chain reaction, and western blotting. Results: In the Morris water maze and nesting experiments, PGG-treated WT mice exhibited significantly improved learning and memory. The structures of 171 glycoprotein fragments in PGG matched the credible score, and typical structures were identified using LC/MS data analysis. According to the proteomic analysis results, 188 DEPs were detected between the model and administration groups, and two downregulated DEPs were related to the Notch signaling pathway. Based on the in vitro verification tests, PGG significantly inhibited the expression of key proteins in the Notch signaling pathway in microglia. Conclusions: PGG could prevent the development of neuroinflammation by inhibiting excessive activation of the Notch signaling pathway, thereby inhibiting neuroapoptosis. Graphical abstract: Image 1 Highlights: The structures of complex ginseng glycoproteins were determined by LC/MS-Methylation cooperation strategy. PGG has shown significant improvement in learning and memory abilities on APP/PS1 mutant mouse models. Label-free results revealed considerable differences in protein levels after PGG treatment compared to the model group. The activity of PGG was related to its inhibition of NOTCH pathway and reduction of neuroinflammation development.